Variety Growth and World Welfare - Broda, Christian; Weinstein, David E (American Economic Review, 2004)
Economists since John Richard Hicks have known that one of the principal means, if not the principal means, through which countries benefit from international trade is by the expansion of varieties. The seminal work of Paul R. Krugman (1979) brought the study of varieties into sharp focus by presenting a simple generalequilibrium model in which countries gain from trade through the import of new varieties. Since then, economists have been hampered in their ability to quantify the impact of new varieties on national welfare by the econometric and data hurdles that need to be surmounted. In this paper, we document some stylized facts about the growth in global varieties which suggest that there may have been substantial welfare gains through the import of new varieties. Moreover, we calculate the impact of increased variety on import prices and find that conventional measures of import price inflation may be dramatically biased upward. Classical international-trade theory postulates that the elimination of trade barriers improves welfare by reducing the wedge between domestic and import prices as well as the ensuing deadweight loss. An entirely different reason for the gains from trade arises from models of monopolistic competition. If consumers value variety and countries cannot produce all varieties due to a fixed cost in the production of each variety, countries stand to gain from trade because it expands the set of available varieties. In these models, the gains hinge crucially on a number of parameters and variables. The first is the elasticity of substitution among varieties. If varieties are highly substitutable, as might be true for varieties of gasoline, then increasing the number of varieties is unlikely to have much of an effect on prices and welfare. Second, quality variation across varieties may matter. Presumably, most Americans care more about having access to French red wine than to Japanese red wine. Finally, import quantities matter as, ceteris paribus, one cares more about variety growth in big sectors than in small sectors. In Broda and Weinstein (2004), we carefully estimate the impact of increased variety in the United States over the period from 1972 to 2001. Using the most disaggregated import data available, we document that the number of varieties imported by the United States, defined as the number of import categories multiplied by the average number of source countries for each category, quadrupled. About half of this increase was due to increases in the number of categories and half due to a doubling of the number of countries from which the United States imported each good. Measuring the impact of this increase on U.S. import prices and welfare is a complex process that we will only discuss briefly here. Essentially, we used Robert C. Feenstra’s (1994) methodology to estimate 30,000 elasticities and then construct an aggregate price index that is robust to common changes in quality variation, the arbitrary splitting of categories, the introduction of new goods, and a host of other data problems. After reconstructing the U.S. import price index, we found that the price of U.S. imports has been falling at a rate 1.2 percent per year faster than one would have thought without taking new varieties into account. To get some sense of the enormity of this bias, consider that the impact of quality adjustments on the consumer price index is estimated to be 0.6 percent per year. Using this adjusted import price index, we estimate the impact of new imported varieties on * Broda: Research Department, Federal Reserve Bank of New York, 33 Liberty Street, New York, NY 10045; Weinstein: Economics Department, Columbia University, 420 W. 118th Street, New York, NY 10027, and NBER. We thank Joshua Greenfield for excellent research assistance. We thank Robert Feenstra and Peter Klenow for excellent comments. 1 “The extension of trade does not primarily imply more goods ... the variety of goods available is (also) increased, with all the widening of life that that entails. There can be little doubt that the main advantage that will accrue to those with whom our merchants are trading is a gain of precisely this kind ... . This is a gain which ‘quantitative economic history,’ which works with index numbers of real income, is ill-fitted to measure, or even to describe” (Hicks, 1969 p. 56).